2008
DOI: 10.1055/s-2008-1061626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Semantic-Based Treatment for Naming Deficits in Aphasia: What Works?

Abstract: This article reviews the basic principles and evidence for the effectiveness of a semantic-based treatment for naming deficits in aphasia. This article focuses on three aspects of semantic-based treatment. First, the theoretical basis for semantic treatment approaches to alleviate naming deficits is explained. Second, the different types of semantic treatment approaches (i.e., substitutive and restitutive treatments) are reviewed. More attention is provided to restitutive treatment approaches, and some ideas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 59 publications
2
23
0
1
Order By: Relevance
“…Another finding of this study was that a small subset of patients showed cross-language generalization only to semantically related translations, suggesting some form of inhibition that did not impact the untrained semantic associates in the untrained language. The observed instances of positive cross-language generalization were explained by the increased spreading activation of both target words and their semantically related neighbours in both the trained language and the untrained language and is consistent with what is known about generalization in monolingual aphasia (Kiran & Bassetto, 2008) and cross-language priming . Explanations for the instances in which no cross-language generalization was observed, or when generalization was only observed to semantically related neighbours of the translations of the trained items, were explained in the context of an interaction between spreading activation and inhibitory control.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another finding of this study was that a small subset of patients showed cross-language generalization only to semantically related translations, suggesting some form of inhibition that did not impact the untrained semantic associates in the untrained language. The observed instances of positive cross-language generalization were explained by the increased spreading activation of both target words and their semantically related neighbours in both the trained language and the untrained language and is consistent with what is known about generalization in monolingual aphasia (Kiran & Bassetto, 2008) and cross-language priming . Explanations for the instances in which no cross-language generalization was observed, or when generalization was only observed to semantically related neighbours of the translations of the trained items, were explained in the context of an interaction between spreading activation and inhibitory control.…”
Section: Introductionsupporting
confidence: 84%
“…Patients received a semantic-based naming treatment in one language (either English or Spanish), and cross-language generalization was examined to the untrained language (Kiran, Sandberg, Ascenso, Kester, & Gray, 2013). Most of the patients showed within-language generalization (i.e., generalization to semantically related items within the same language), a finding that is consistent with theories of monolingual aphasia rehabilitation (Kiran & Bassetto, 2008;Maher & Raymer, 2004). However, fewer than half of the patients showed cross-language generalization to translations or to semantically related translations.…”
Section: Introductionmentioning
confidence: 77%
“…However, on the basis of reviews of single-word-naming treatments and verb-focused treatments, VNeST appears to exhibit relatively robust generalization to noun and verb naming, sentence production, and lexical retrieval within sentences in discourse, although more research is needed. See Conroy et al (2006) and Webster and Whitworth (2012) for verb treatment reviews, Boyle (2010) for a review of semantic feature analysis, and Druks (2002), Kiran and Bassetto (2008), and Nickels (2002) for reviews of single-word approaches to treatment.…”
Section: Vnest Outcomes Summarymentioning
confidence: 99%
“…More precisely, semantic and phonological therapies are effective for central semantic deficits and phonological or mixed phonological and semantic treatments are effective for phonological encoding disorders [5,6,[12][13][14][15]. However, the relationship between the nature of impairment of word retrieval and its appropriate treatment is widely debated [10,16,17].…”
Section: Introductionmentioning
confidence: 99%